The Effecttiveness of Education Basic Life Support (BLS) Simulation Toward Increasing of the Youth Red Cross Student Abilities - Devi, Ni Nyoman Chrisna Purnama; Idris, Baiq Nurainun Apriani; Supriyadi, Supriyadi (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Heart failure is deadly disease and was still as the main cause of death in society, however, low level of knowledge about treating heart failure victims makes the crisis treatment was failed to help cardiopulmonary resuscitation (CPR). People's understanding, especially the younger generation, about basic life support needs to be developed and trained so that they can help people who suffered cardiac arrest anywhere. Objective: this research was to determine the effectiveness of education of basic life support simulation toward the increasing of students especially the youth of red cross teenagers of the school abilities. Method: The research design used was experimental with one group pre-test post-test design. Result: The statistical test used was Wilcoxon signed rank test to determine differences on knowledge levels before and after treatment. The research results obtained that p value of 0.000 (<0.05), it’s showing that there is effectiveness of education through basic life support simulations in increasing the abilities of teenage red cross students. Conclusions: this research obtained that the simulation can improve teenage red cross student’ s basic life support abilities.